The use of prophylactic systemic antibiotics in compound depressed skull fractures in infancy and childhood - J. Píndaro P. Plese; Robin P. Humphreys (Arquivos de Neuro-Psiquiatria)
The authors described their experience with the use of prophylactic antibiotics in children with compound depressed skull fractures. The analysis of the results of the treatment of patients with or without systemic antibiotics and with or without the replacement of the bone fragments showed no difference in the infection rate, any one was the method used.